Jogos de empresas: estudo das suas contribuições para o curso de pós-graduação lato sensu em administração de empresas - Perez, Leandro Reale (2007)
The objective of this work is to study the games of companies and their benefits for enterprise management, since the use in the courses of Graduation Lato-Sensu in Business administration, focusing the analysis on the student s point of view. The study of this subject justifies itself, because there are few reports available in literature concerning the perception of students in the evaluation of this methodology as a learning tool that collaborates with the development of competences and abilities, which are important to place the students in the business market. The considered method of research is the case study. This study has been developed taking as reference the experience of the Armando Alvares Penteado Foundation - FAAP in São Paulo and São José dos Campos, which offer the discipline business simulation in their courses of Post-Graduation in Business administration. The research had a sample size of 80 (eighty) students who had taken business simulation classes in the year of 2006. This institution of education was chosen by being one of the precursors in the use of the Business simulation tools in Brazil and also by the fact of never having participated in research about this subject. It has been verified that the business simulation do not substitute any other discipline. However it adds value in the course composition of Graduation in Administration course specially supporting the National Curricular Lines (BRASIL, 2005) in its needs, therefore, questions between theory and practice using the meaningful learning, fit the student s needs, despite the fact that this tools improve student s management skills for business market